Psychosocial Intervention for Dual-diagnosis Client: A Case from Counseling Practice - Farhana Sabri; Sareh Safwan A. Seman (Auctores Publishing, 2024)
This article describes a female university student aged 22-year-old. The client was referred by a psychiatrist, from Addiction Clinic, Psychiatry & Mental Health, Hospital Sultanah Bahiyah for crisis management for panic attacks and supportive counseling as well as motivational interviewing on her substance use. The client presented with complaints of having panic symptoms such as hand tremors, sweating, unable to talk to anyone, and dizziness. She also complained of having difficulty sleeping due to fear of having a nightmare of traumatic events, overthinking, low self-esteem, and loss of focus in her study. The assessment was done on both the informal and formal levels. For informal assessment, an intake interview was conducted to gain information about her background and substance use history; the mental status examination was done, a life event chart was used, and for the purpose of formal assessment TAPS (Tobacco, Alcohol, Prescription medication, and other Substance use Tool) and Stages of Change was used. The score of each test suggests that the client is having substance use problems (i.e alcohol & nicotine) and her stage of change is contemplation. The primary diagnosis is F10.10, Alcohol Use Disorder, Mild, and the secondary diagnosis is F43.0, Acute Stress Disorder. In terms of intervention plan rapport building, supportive psychotherapy, psychoeducation, relaxation techniques, addiction cycle, and relapse prevention technique were used. The overall outcome of the process was an improvement of her alcoholic symptoms due to traumatic events and desirable behavior in getting sober from alcohol use. After the sixth counseling session, her stage of change progressed from contemplation stage to preparation.